2009
DOI: 10.1203/pdr.0b013e3181b337b9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Suction Method, Catheter Size, and Suction Pressure on Lung Volume Changes During Endotracheal Suction in Piglets

Abstract: ABSTRACT:We aimed to identify the effect of suction pressure and catheter size on change in lung volume during open and closed endotracheal suction. Anesthetized piglets (n ϭ 12) were intubated with a 4.0-mm endotracheal tube. Lung injury was induced with saline lavage. Three suction methods (open, closed in-line, and closed with a side-port adaptor) were performed in random order using 6, 7, and 8 French gauge (FG) E ndotracheal tube (ETT) suction is performed periodicallyin patients receiving mechanical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…It can be related to that in the study group, there was increased probabilities of improving inspired volume of air as evidenced by decreased time of patient's disconnection from ventilator, suctioning was done for 10 to 15 seconds, external diameter of the suction catheter was less than half of the internal diameter of the patient's tracheal tube, and suction pressure was controlled from 120 to 150 mmHg. Copnell B. et al (22) reported that the effect of suction method, force, and tube size on lung volume changes during ES in piglets and found that closed suction preserved more lung volume than open one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be related to that in the study group, there was increased probabilities of improving inspired volume of air as evidenced by decreased time of patient's disconnection from ventilator, suctioning was done for 10 to 15 seconds, external diameter of the suction catheter was less than half of the internal diameter of the patient's tracheal tube, and suction pressure was controlled from 120 to 150 mmHg. Copnell B. et al (22) reported that the effect of suction method, force, and tube size on lung volume changes during ES in piglets and found that closed suction preserved more lung volume than open one.…”
Section: Discussionmentioning
confidence: 99%
“…It was a developed tool by the researcher after reviewing the related literature (2,3,10,(21)(22)(23) . It was used to gather data of cardiorespiratory parameters to compare between actual routine method practiced by nurses in ICU and guidelines based method that are restricted to evidenced based recommendations.…”
Section: Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…In open suctioning, volume loss is independent of catheter size. 56 This may be explained by the probable presence of turbulent flow between the ETT and suction catheter during closed suctioning. 52 The concept that closed suctioning is better because it prevents volume loss may be incorrect.…”
Section: Open Versus Closed Suctioningmentioning
confidence: 99%
“…Not surprisingly, open suctioning produced a greater lung-volume loss. 56 Note, however, that 4 of the 10 HFOV patients were receiving muscle relaxants, and those paralyzed patients had the longest recovery times. 53 This could correlate to the fact that paralyzed patients are often sicker.…”
Section: Open Versus Closed Suctioningmentioning
confidence: 99%